2020
DOI: 10.1038/s41390-020-0943-1
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29b is associated with perinatal inflammation in extremely preterm infants

Abstract: Background: Inflammation is strongly associated with premature birth and neonatal morbidities. Increases in infant haptoglobin (Hp&HpRP) and IL-6 levels are indicators of intra-amniotic inflammation (IAI) and have been linked to poor neonatal outcomes. Inflammation causes epigenetic changes, specifically suppression of miR-29 expression. The current study sought to determine whether miR-29b levels in cord blood or neonatal venous blood are associated with IAI, identified by elevated IL-6 and hapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…It has also been shown that the miRNA profiles of the placenta 31 , amniotic fluid 34 , and maternal serum 32 , whole blood and monocytes 35 differ between preterm and full term births. Although the lasting effect on PTB on DNA methylation pattern 19,36 and subjects' health 37 have been studied, only a few studies analyzing the associations of PTB with the subjects' circulatory miRNA profile have been conducted on newborns [38][39][40][41] and one case-control study (n = 50) with 4 selected miRNAs in young adults 42 .…”
mentioning
confidence: 99%
“…It has also been shown that the miRNA profiles of the placenta 31 , amniotic fluid 34 , and maternal serum 32 , whole blood and monocytes 35 differ between preterm and full term births. Although the lasting effect on PTB on DNA methylation pattern 19,36 and subjects' health 37 have been studied, only a few studies analyzing the associations of PTB with the subjects' circulatory miRNA profile have been conducted on newborns [38][39][40][41] and one case-control study (n = 50) with 4 selected miRNAs in young adults 42 .…”
mentioning
confidence: 99%
“…miR-29a-3p has been reported in a multitude of diseases, ranging from intrauterine inflammation in extremely preterm infants ( 15 ) and airway epithelial remodeling in chronic obstructive pulmonary disease ( 16 ) to proliferation and differentiation in retinal progenitors ( 17 ). Studies have reported that miR-29a-3p could be a therapeutic tool for certain diseases, such as pulmonary fibrosis ( 14 ) and Alzheimer's disease ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are small noncoding RNAs of about 22 nucleotides that are implicated in developmental processes such as neurogenesis and myogenesis, as well as in many pathological processes [105]. Amongst all noncoding RNAs, miRNAs are the most well studied for their regulatory roles in controlling gene expression by either targeting mRNAs for degradation or blocking their translation.…”
Section: Micrornas In Cpmentioning
confidence: 99%
“…Furthermore, miR-200c overexpression inhibited skeletal muscle differentiation [114]. Satellite-cell proliferation is stimulated by the overexpression of miR-29c, which represses the expression of the atrophy-related genes, implying an association between lower miR-29 levels and CP [105,115]. This miRNA has been implicated in regulation of extracellular matrix deposition and its expression may be inhibited as a result of inflammation.…”
Section: Micrornas In Cpmentioning
confidence: 99%